2020
DOI: 10.3390/met10020235
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Behavior from Selected Foundry Sands with Alkali Silicate-Based Inorganic Binders

Abstract: The automotive industry is one of the most important customers for the foundry industry. In particular, casting of engine parts for combustion engines is one of the most demanding areas of casting technology. New generation of engine blocks and cylinder heads are getting geometrically more complicated in order to maintain or even increase performance. With the increased complexity, the strain for the casting molds is growing and the widely used technology of core making with standard silica sands is, for sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…However, in case of castings that are not subject to further machining porosity has to be dealt with by production technology modification, best before the casting process [3]. However, the porosity minimization task is complicated and it requires taking into account the material chemical composition, casting temperatures, inoculation method, risers, as well as the mould proper material and design [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, in case of castings that are not subject to further machining porosity has to be dealt with by production technology modification, best before the casting process [3]. However, the porosity minimization task is complicated and it requires taking into account the material chemical composition, casting temperatures, inoculation method, risers, as well as the mould proper material and design [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…They present the results of permeability based on the outlet velocity of the measured samples and compare it with the simulated results of permeability. Vaskova et al [ 19 ] studied the effect of combining coarse sand with fine sand and reported a decrease in permeability with an increasing percentage of fines content. Their results show that after a certain amount of increased fines, the permeability did not reduce much for the sand mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the properties of the base sand are considered. The granulometric properties (grain size distribution, grain shape) have an overwhelming effect on the binder demand, the flowability of the sand mixture during core shooting, and, in this way, on the bulk density, mechanical properties, and surface characteristics of the sand cores [ 10 , 25 , 26 ]. Another important factor is the impurity content of the sand, as silica sands tend to contain different minerals as contaminants, such as potash, alkali feldspars, soda, which can occur in the form of separate particles or as a layer on the surface of the silica grains.…”
Section: Introductionmentioning
confidence: 99%